MARKET STRUCTURE IN ISLAMIC PERSPECTIVE: A CRITICAL EXAMINATION OF THE TERMS PERFECT AND IMPERFECT COMPETITION - Sri Yayu Ninglasari; M. Fikri Himmawan; Luthfi Nur Rosyidi; Aas Nur Asyiah (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2023)
The purpose of this study is to examine the terms "perfect" and "imperfect" competition in the market structure from an Islamic economic perspective. This study employed a qualitative approach to library research as its methodology. The results of the literature review indicate that the structure of perfect competition has a close relationship with the Islamic market concept. This proximity is reflected in the price, which is determined according to the hadith of the Prophet Muhammad by supply and demand. In addition, it is believed that perfect market competition is a market structure that can benefit both consumers and producers. Moreover, elements of imperfect competition that can oppress consumers, such as monopolies, oligopolies, and monopolistic practices, must be avoided. In Islamic economics, however, there is no concept of competition because it is synonymous with war, fighting, and dumping, so the term "competition" in the concept of market structure is inappropriate. For this reason, a new concept is required, namely the ta'awun market, in which the market in Islamic economics should be a place and a means of mutual assistance.Keywords:Â Market structure, Islamic perspective, perfect competition, imperfect competitionÂ